2013
DOI: 10.1099/mic.0.062695-0
|View full text |Cite
|
Sign up to set email alerts
|

Arginine deiminase inhibits Porphyromonas gingivalis surface attachment

Abstract: The oral cavity is host to a complex microbial community whose maintenance depends on an array of cell-to-cell interactions and communication networks, with little known regarding the nature of the signals or mechanisms by which they are sensed and transmitted. Determining the signals that control attachment, biofilm development and outgrowth of oral pathogens is fundamental to understanding pathogenic biofilm development. We have previously identified a secreted arginine deiminase (ADI) produced by Streptococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 56 publications
(65 reference statements)
3
15
0
Order By: Relevance
“…We found that S cristatus arginine deiminase (ArcA) can repress FimA expression in several P. gingivalis strains, including strains expressing fimA types I, II, and III . Similar results were later observed by the Davey lab, in which they reported a downregulation of P. gingivalis genes encoding the major ( fimA ) and minor ( mfa1 ) fimbriae by Streptococcus intermedius ArcA. Our data from a peptide array showed that an eleven amino acid peptide with the native sequence of streptococcal ArcA, which we designate streptococcal ArcA derived anti‐ P. gingivalis peptide (SAPP), not only repressed fimA and mfa1 expression but also repressed mfa1, rgpA/B, and kgp expression in P. gingivalis .…”
Section: Introductionsupporting
confidence: 87%
“…We found that S cristatus arginine deiminase (ArcA) can repress FimA expression in several P. gingivalis strains, including strains expressing fimA types I, II, and III . Similar results were later observed by the Davey lab, in which they reported a downregulation of P. gingivalis genes encoding the major ( fimA ) and minor ( mfa1 ) fimbriae by Streptococcus intermedius ArcA. Our data from a peptide array showed that an eleven amino acid peptide with the native sequence of streptococcal ArcA, which we designate streptococcal ArcA derived anti‐ P. gingivalis peptide (SAPP), not only repressed fimA and mfa1 expression but also repressed mfa1, rgpA/B, and kgp expression in P. gingivalis .…”
Section: Introductionsupporting
confidence: 87%
“…In addition, the difference in optimum temperature and pH of ArcA activity was observed between the assay reaction with and without DTT (data not shown). Our data confirmed the previous results reported by Cugini et al [2013] that ArcA activity was rapidly lost in a nonreducing environment and the addition of DTT greatly increased enzymatic activity. These results indicated that the SS2 ArcA was highly sensitive to oxidizing conditions and Cys399 residue could play an essential role in the SS2 ArcA catalysis.…”
Section: Amino Acid Sequence Alignment Of Arcasupporting
confidence: 83%
“…This phenomenon of inhibition of twitching motility by arginine has been reported by Cugini et al (2012), in which they observed that the arginine deiminase secreted by Streptococcus intermedius inhibited biofilm formation in the commensal pathogen Porphyromonas gingivalis. This is achieved via downregulation of genes encoding the major (fimA) and minor (mfa1) fimbriae, both of which are required for proper biofilm development (Cugini et al, 2012). Arginine deiminase is an enzyme that catalyzes the hydrolysis of L-arginine to L-citrulline and ammonia gas (Gong et al, 2000).…”
Section: Discussionmentioning
confidence: 77%